HUKUM BAHASA ISYARAT DALAM AKAD NIKAH BAGI DISABILITAS TUNA RUNGU: (Studi Kasusu di Madrasah Tuna Rungu Assabikunal Awwalun Tasikmalaya). - Lukmanul Hakim; Kustiawan Adinata (Program Studi Hukum Keluarga Islam, 2024)
The marriage contract is a harmony and agreement between two brides using a language that can be understood by both parties, including by using sign language because one cannot use spoken language because of a disability, namely not being able to hear. In the context of Islamic law, the pronunciation of ijab and qabul in the marriage contract must be done clearly. The purpose of the research; This is to understand the practice of sign language used by people with deaf disabilities in the marriage contract procession at Madrasah Deaf Assabikunal Awwalun and sign language laws in carrying out marriage contracts. The research method used is qualitative with a normative sociological approach, namely examining the applicable legal provisions and what happens in reality in society. The results of the study show that 1) in general, the marriage procedure is the same, it's just that when you find a difference, there is something that causes it to happen. For example, a marriage was held by a deaf couple with disabilities who used sign language as a means of ijab qabul. As taught by the assabikunal awwalun madrasah to its students to use sign language in carrying out their ijab qabul. 2) In the study of Islamic law and laws and laws, it is allowed for marriage contracts to use sign language in carrying out ijab qabul, provided that the sign language can be understood by all parties.